Implementasi Penetapan Calon Kepala Desa di Desa Pulo Reudeup Kecamatan Kuta Blang Kabupaten Bireuen: Analisis UU No 6 Tahun 2014 dan Qanun No 4 Tahun 2009 - Haris Munandar; Nurdin, Safriadi; Iswandi Iswandi (Siyasah Wa Qanuniyah, 2024)
One of Aceh's qanuns that regulates the method of election and conditions of geuchik is Aceh Qanun No. 4 of 2009 on the Procedures for the Election and Dismissal of Keuchik in Aceh. This research highlights the criteria for a proper village head/Keuchik in accordance with the legal provisions of the qanun. This study aims to describe the understanding of the community and the Keuchik Election Committee (P2K) of the provisions of the nomination of village heads and the implementation of the determination of candidates for village heads in Pulo Reudeup Village, Kuta Blang District, Bireuen Regency. The research method uses a qualitative approach through interviews and documentation. The results showed that the community's understanding of the nomination requirements was good, but the election mechanism was still poorly understood. The implementation of the determination of village head candidates needs to be improved to be in accordance with the applicable qanun.